EVALUATION OF TOMATO RESPONSE TO DEFICIT IRRIGATION AT HUMBO WOREDA, ETHIOPIA - Kifle, Tamirneh (International Journal of Research -GRANTHAALAYAH, 2018)
Water scarcity, erratic rainfall distribution and better management of water are the most sever constraint for the development of agriculture. To cope with scarce supplies, deficit irrigation is an important tool to achieve the goal of reducing irrigation water use and increase water use efficiency (WUE) under scarce water resources. This research was carried out at Southern Agricultural Research Institute of Areka Agricultural Research Center of Hubo Woreda in farmers’ fields during 2016/2017–2017/2018 to identify the level of deficit irrigation which allow achieving optimum Tomato yield. The experimental design was arranged in RCBD with four treatments with three replications. The irrigation treatments were 100 % ETc, 85 % ETc, 75 % ETc and 50 % ETc. The result showed that a maximum fruit yield of 43.4 ton/ha was obtained under full irrigation. A deficit irrigation strategy applied at 85%, 70% of crop water requirement gives relatively better fruit yield i.e. 34.2 ton/ha and 32.1 ton/ha. For Tomato in water scarce area applying 85% and 70% of crop water requirement is recommended with a minimum reduction of yield.